Improving conflict support environments with information regarding social relationships - Gomes, Marco (2014)
"Advances in artificial intelligence : IBERAMIA 2014 : 14th Ibero-American Conference on AI, Santiago de Chile, Chile, November 24-27, 2014, proceedings", ISBN 978-3-319-12026-3